The The Supplementation of Micro-encapsulated Organic Acids and Essential Oils Mixture on Growth Performance and Gut Health of Broiler Chickens Fed High Wheat and Corn Distiller’s Dried Grain Diet - Preesong, Pattaveekan; Lertwatcharasarakul, Preeda; Seemacharoensri, Akaradet; Tactacan, Glenmer; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2022)
Aims of this study were to evaluate the supplementation of micro-encapsulated organic acids and essential oils mixture on growth performance and gut health of broiler chickens fed diet containing high wheat and corn distiller’s dried grain. A total of 1,050 male broilers (Ross 308) were allocated into 3 treatments with 14 replicates per treatment using a Completely Randomized Design. The treatments were: 1) corn-soybean meal basal diet (CS), 2) CS with high wheat and corn distiller’s dried grain diet (WD), 3) WD with 300 mg/kg of micro-encapsulated organic acids and essential oils mixture (WD + EOS). Overall performance (1-35 DOA), feed intake and feed conversion ratio of bird fed WD and WD + EOS diets were highly significant increased (P<0.01) when compared with CS diet. There were no significant differences in body weight gain, percentage of culling and percentage of mortality. In term of evaluation of gut health in intestinal jejunum at 35 DOA, tight junction mRNA relative gene expression of claudin-1 and occludin were up-regulated (P<0.01) in WD + EOS diet. Birds fed WD diet had a higher cecal ammonia, cadaverine and putrescine levels than that of CS group (P<0.05). The supplementation of EOS in WD diet lowered putrescine level when compared to that of WD group (P<0.01) but did not differ from the CS group (P>0.05). The results showed that the supplementation of micro-encapsulated organic acids and essential oils mixture improved gut health and reduce the negative effects of high wheat and corn’s distiller dried grain levels in broiler chicken diets.